(untitled) (The Lumbini Journal of Business and Economics, 2025)
Purpose: The study aims to investigate the relationship between leadership style and academic performance with the mediating effect of class engagement. Methods: Stratified sampling technique was used, targeting 253 graduates’ management students of Butwal out of total population 625.Data was analyzed using a seven-point Likert scale in a questionnaire. Similarly, a descriptive and causal comparative study design was employed, along with a wide range of statistical measures, such as mean, standard deviation, correlation, and regression, which are selected for reliable data analysis using IBM SPSS Statistics version 20 and Smart PLS student version. Results: The results reveal that there is positive and significant effect of charismatic and emotional leadership on academic performance with the mediating effect of class engagement. Likewise, transformational leadership does not show any effect on academic performance. Conclusion: The research concludes that the emotional leadership is most influencing determinants of academic performance of Professor. So, the colleges and universities should prefer the emotional leadership of the professor to enhance the academic performance.